2012
DOI: 10.1111/j.1365-2761.2012.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of casein and αs2 casein hydrolysates against the infectious haematopoietic necrosis virus, a rhabdovirus from salmonid fish

Abstract: Salmonid fish viruses, such as infectious haematopoietic necrosis virus (IHNV), are responsible for serious losses in the rainbow trout and salmon-farming industries, and they have been the subject of intense research in the field of aquaculture. Thus, the aim of this work is to study the antiviral effect of milk-derived proteins as bovine caseins or casein-derived peptides at different stages during the course of IHNV infection. The results indicate that the 3-h fraction of casein and α(S2) -casein hydrolysat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Besides this study, very little published work is available on the antiviral treatments for rabies. There have, however, been some AMPs identified for other viruses in the Rhabdovirus family, including casein and α s2 -casein, which can drastically inhibit the replication of the infectious haematopoietic necrosis virus in salmonid fish [256]. Another study also found that human α-defensin-1 has antiviral activity against the haemorrhagic septicaemia virus [257].…”
Section: Neglected Tropical Diseasesmentioning
confidence: 99%
“…Besides this study, very little published work is available on the antiviral treatments for rabies. There have, however, been some AMPs identified for other viruses in the Rhabdovirus family, including casein and α s2 -casein, which can drastically inhibit the replication of the infectious haematopoietic necrosis virus in salmonid fish [256]. Another study also found that human α-defensin-1 has antiviral activity against the haemorrhagic septicaemia virus [257].…”
Section: Neglected Tropical Diseasesmentioning
confidence: 99%
“…Antiallergenic properties are measured in vitro determining IgE content by the reverse enzyme allergosorbent, ELISA, or enzyme allergosorbent tests (Falagiani et al., ; Wigotzki, Steinhart, & Paschke, ), or in vivo by measuring indexes of spleen and thymus status, such as changes in weight, hemolysin content, changes in optical density as a result of macrophage activity, and release of histamine from mast cells (Pan et al., ). Cytotoxic activity and apoptosis have been assessed measuring cell viability and proliferation by staining, (3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide assay, acid phosphatase assay, neutral red uptake assay, lactate dehydrogenase assay, incorporation of [ 3 H] thymine, NK assay, or JAM test (Bateman et al., ; Chalamaiah et al., ; Hagiwara, Shinoda, Fukuwatari, & Shimamura, ; Hou et al., ; Repetto, del Peso, & Zurita, ; Richardson et al., ; Rodríguez Saint‐Jean et al., ; Yang, Sinai, & Kain, ), apoptosis by the annexin V test and caspase assay (Green & Steinmetz, ; Hartmann, Wal, Bernard, & Pentzien, ), mitochondrial transmembrane potential (Hartmann et al., ; Richardson et al., ), or DNA synthesis and damage (Hsien, Ho, Lai, & Yen, ).…”
Section: Measuring the Effects Of Bioactive Peptidesmentioning
confidence: 99%
“…At this time, they were used in the food industry to inhibit the oxidation of lipids of food processed as oil and snack products and for other purposes [10,11]. Now, there is interest to find new antioxidant compounds of natural sources such as food proteins and hydrolysates [12,13,14]. The food hydrolysates have an interest in the food industry for different purposes for their biological activities.…”
Section: Introductionmentioning
confidence: 99%